Antrian Digital Berbasis Wireless di Pukesmas Pembantu (PUSTU) Dauh Puri Denpasar Barat - Made Dika Nugraha; Kadek Agus Mahabojana Dwi Prayoga; I Nyoman Angga Prabawa (Postgraduated Community Service Journal, 2022)
Accumulation of the number of patient queues at the Pukesmas Pembantu (Pustu) Dauh Puri. This is due to fewer service facilities compared to the number of requests so that the time used by patients in the queue becomes unsystematic. The registration process and ordering queue numbers are still done manually without implementing a wireless system with a button keypad, where the manual queue machine has been printed first, first taken by the patient. Come to the puskesmas first to be able to take the queue number, then wait for registration by being called by the puskesmas officer without using an automatic dialing machine that is integrated with the queue machine so that patients have to wait their turn to be called in to get services from doctors in the absence of a seven segment display for petrified showing the last queue number and the registration counter to be addressed by the patient. The method that will be used in making this tool is a method of discussion and workshop-based tool work. The stages of the activity will be as follows: First, the proposer will provide the basic concept of the importance of digital technology knowledge. Second, the proposer will assemble the tools according to the distribution of the criteria for patients and clinics. Third, the proposer will provide training on the use of tools already using a wireless system. Fourth, if the PkM activity is about to end, a questionnaire will be distributed as an evaluation material in the activity. The solution that will be carried out is to overcome the services of elderly, general and toddler patients, namely the service of making a wireless-based queue number machine by installing an installation system, providing training to community health workers regarding the running and maintenance process.